Digital finance and agri-food value chains: Case studies from Kenya - Wairimu, Edith (International Food Policy Research Institute, 2025)
Kenya’s agrifood systems are broad and diverse, including both staple food crops and high-value exports which are essential to the economic and social advancement of the nation. The agricultural sector em ploys more than 40 percent of Kenya's workforce, including more than 70 percent of rural residents, and accounts for about 33 percent of the country's GDP (FAO, 2023a; FAO, n.d.). The growth of Kenya’s agrifood system is largely driven by domestic market demand rather than exports, a trend driven by rapid urbanization and rising income opportunities in the rural nonfarm sector, which are leading to shifts in dietary preferences and are expected to further influence ongoing structural transformation (Diao et al., 2023).